Errors in Aerosol Inhaler Use and Their Effects on Maternal and Fetal Outcomes among Pregnant Asthmatic Women (Subanalysis from QAKCOP Study) - Wanis H. Ibrahim; Fatima Rasul; Mushtaq Ahmad; Abeer S. Bajwa; Laith I. Alamlih; Anam M. El Arabi; Dhabia Al-Mohannadi; Mohammed Y. Siddiqui; Israa S. Al-Sheikh; Azdin A. Ibrahim (Canadian Respiratory Journal)
Data on inhaler technique and its effects on maternal and fetal outcomes during pregnancy are seldom reported. The primary objective of this study was to evaluate inhaler technique and identify errors in inhaler use among pregnant women with asthma. Secondary objectives were to identify factors associated with poor inhaler technique and study the association between inhaler technique and maternal and fetal outcomes. This was a cross-sectional, face-to-face, prospective study of 80 pregnant women with physician-diagnosed asthma. Seventy-three and 41 asthmatic pregnant women reported using pressurized metered dose inhalers (pMDIs) and dry powder inhalers (DPIs), respectively. Overall, wrong inhaler technique was observed in 47 (64.4%) subjects. Among pMDI users, correct inhaler use was observed in only 26/73 (35.6%) of the patients, with lack of coordination between inhalation and generation of the aerosol and failure to breathe out gently before using the inhaler, being the most common errors. Among DPI users, 21 (51.2%) demonstrated correct inhaler use, with failure to perform a breath-hold for 10 seconds after inhaling the powder and to exhale gently before using the inhaler being the most common errors. Significant associations between inhaler technique and patient’s understanding of asthma medications and the kind of follow-up clinic (respiratory versus nonrespiratory clinic) were found. No significant associations between inhaler technique and various maternal and fetal outcomes or asthma control were found. In conclusion, improper inhalation technique is significantly prevalent in pregnant asthmatic women, particularly among those being followed in nonspecialized respiratory clinics. The lack of significant association between the inhaler technique and asthma control (and hence maternal and fetal outcomes) may simply reflect the high prevalence of uncontrolled asthma and significant contribution of other barriers to poor asthma control in the current patient’s cohort. Multidisciplinary management of asthma during pregnancy with particular emphasis on patient’s education is imperative.